Pengaruh Pendidikan Entrepreneurship dan Lingkungan Sosial terhadap Minat Berwirausaha - Henny Wati; Patria Nagara; Sari Rahayu; Muhammad Hendra (Jurnal Informatika Ekonomi Bisnis, 2023)
This research is entitled The Influence of Entrepreneurship Education and the Social Environment on Interest in Entrepreneurship in Students of the Faculty of Health Sciences at the University of West Sumatra. This research is motivated by the need for students in the faculty of health sciences to be able to create their own job opportunities with the abilities or education they have received. No need to wait for the relevant agency to open job vacancies. This research uses a quantitative type of research. The data taken was primary data by distributing questionnaires to students at the Faculty of Health Sciences at the University of West Sumatra. This research carried out research instrument tests, classical assumption tests, hypothesis tests using SPSS version 21. The research results stated that looking at the test results that had been carried out proved that both variables had a significant effect partially or simultaneously, and it could also be seen that the Adjusted R Square was 0.403 or amounting to 40.3%. This means that the variable interest in entrepreneurship is influenced by entrepreneurship education and the social environment and the remaining 50.7% is influenced by other variables outside of this research variable.